2011
DOI: 10.1177/2151458511421908
|View full text |Cite
|
Sign up to set email alerts
|

A Geriatric Multidisciplinary and Tailor-Made Hospital-At-Home Method in Nursing Home Residents With Hip Fracture

Abstract: Introduction: Nursing home residents represent a large proportion of patients hospitalized with hip fracture. Generally, residents do not achieve the same physical ability level as before their fracture and have an increased risk of death within few days after discharge. This study aims to compare 2 new approaches to geriatric intervention in residents with hip fracture. . Median LOS was 2 days in both the groups. A total of 7 follow-up visits were performed with tailor-made intervention versus 3 visits with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The majority of included studies describe ESD services (12/15), and the remainder describe HaH type services. Two of these studies self‐identified their service as “Hospital at Home”, but described ESD‐type services, where patients were admitted to hospital for a period prior to being managed at home. These two services have therefore been analyzed as ESD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of included studies describe ESD services (12/15), and the remainder describe HaH type services. Two of these studies self‐identified their service as “Hospital at Home”, but described ESD‐type services, where patients were admitted to hospital for a period prior to being managed at home. These two services have therefore been analyzed as ESD.…”
Section: Resultsmentioning
confidence: 99%
“…Physiotherapy roles: The most commonly reported physiotherapist role (in 46.7% of included studies) was conducting baseline and outcome measure assessments for the study . These assessments included the modified Barthel Index and Rankin Scale, Borg rating scale, Mini Mental State Examination, nine‐hole peg test, Katz ADL index, 10m walk test and Sickness Impact profile, among others.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations